Can AI Reduce Surgical Errors in Operating Rooms? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The integration of artificial intelligence (AI) into healthcare has spurred a transformative wave, with surgery being one of the most promising frontiers. Su...
Keywords: AI in Surgery and Robotics; Reduce; Surgical; Errors; Artificial Intelligence; Machine Learning; Healthcare